РОЛЬ И МЕСТО АРХИТЕКТОРА СИНАНА В ОСМАНСКОМ ЗОДЧЕСТВЕ (World Science, 2016)
Architect Sinan is outstanding representative of architecture of the Ottoman period. He left an indelible mark in the history of architecture. In his works he used gained experience and went even further. The cathedral mosque of Kanuni Sultan Suleiman is the greatest of Sinan’s creations, his pride, located on the low hill near Khaleej.Data on his activity which reached us specify that he wasn’t always attended construction of his own creations. Throughout the 50-year activity Sinan participated in all the architectural innovations of the Ottoman Empire, he also created a huge number of mosques, turbeh, caravanserais, bridges, water pipelines and other residential and religious buildings.